2019 IEEE 16th International Symposium on Biomedical Imaging (ISBI 2019) 2019
DOI: 10.1109/isbi.2019.8759274
|View full text |Cite
|
Sign up to set email alerts
|

Self-Attention Equipped Graph Convolutions for Disease Prediction

Abstract: Multi-modal data comprising imaging (MRI, fMRI, PET, etc.) and non-imaging (clinical test, demographics, etc.) data can be collected together and used for disease prediction. Such diverse data gives complementary information about the patient's condition to make an informed diagnosis. A model capable of leveraging the individuality of each multi-modal data is required for better disease prediction. We propose a graph convolution based deep model which takes into account the distinctiveness of each element o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 9 publications
(21 reference statements)
0
52
0
Order By: Relevance
“…Geometric matrix completion (GMC): Geometric deep learning [32] is a novel field of deep learning, and has been introduced for computer-aided diagnosis in medicine only recently [33]. In previous work, we have shown that it is advantageous to construct multiple population graphs from meta-features of patients [34,35]. We further proposed GMC [36] (denoted in the following as SingleGMC) to alleviate the common problem of missing values in medical data sets [37].…”
Section: Classification Methodsmentioning
confidence: 99%
“…Geometric matrix completion (GMC): Geometric deep learning [32] is a novel field of deep learning, and has been introduced for computer-aided diagnosis in medicine only recently [33]. In previous work, we have shown that it is advantageous to construct multiple population graphs from meta-features of patients [34,35]. We further proposed GMC [36] (denoted in the following as SingleGMC) to alleviate the common problem of missing values in medical data sets [37].…”
Section: Classification Methodsmentioning
confidence: 99%
“…Meanwhile, image data can be represented as a graph structure appropriate for the use of GNNs. Therefore, GNNs have an extensive application space in the field of medical imaging, such as image segmentation ( Gopinath et al, 2019 ; Wang et al, 2019b ; Tian et al, 2020a , b ), abnormal detection ( Wu et al, 2019 ) of MRI images and pathological images, classification ( Shi et al, 2019 ; Zhou et al, 2019 ; Adnan et al, 2020 ) and visualization ( Levy et al, 2020 ; Sureka et al, 2020 ) of histological images, analysis of surgical images ( Zhang et al, 2018 ), image enhancement ( Hu et al, 2020 ), registration ( Hansen et al, 2019 ), retrieval ( Zhai et al, 2019 ), brain connection ( Ktena et al, 2017 , 2018 ; Li X. et al, 2019a ; Mirakhorli and Mirakhorli, 2019 ; Grigis et al, 2020 ; Li et al, 2020 ; Zhang and Pierre, 2020 ; Zhang et al, 2021 ) and disease prediction ( Parisot et al, 2017 ; Kazi et al, 2018 , 2019a , b , c ; Anirudh and Thiagarajan, 2019 ; Yang et al, 2019 ; StankeviÄŤiĹ«tÄ— et al, 2020 ; Zhang and Pierre, 2020 ; Zhang et al, 2021 ), etc.…”
Section: Typical Application Of Gnns In Bioinformaticsmentioning
confidence: 99%
“…Since then, the use of population graph methods for disease prediction has become the choice of many researchers. Kazi et al (2018) used a multi-level parallel GCN model to optimize the extraction of correlation information between nodes, which introduced an automatic learning layer for weight distribution and the attention mechanism for utilizing the features of each multimodal data ( Kazi et al, 2019c ). Aiming at the problem of insufficient feature extraction caused by fixed neighborhoods in GCN model, InceptionGCN ( Kazi et al, 2019a ) was proposed by Kazi et al, which considered the receptive field convolution kernels of different dimensions and utilized two aggregation methods to process all the features obtained by a convolution kernel.…”
Section: Typical Application Of Gnns In Bioinformaticsmentioning
confidence: 99%
“…As shown in Fig. 1(a), [8] concatenated the node embeddings directly, and both [12] and [22] adopted attention-based fusion mechanism like Fig. 1…”
Section: Introductionmentioning
confidence: 99%